The co-occurrence of Attention-Deficit/Hyperactivity Disorder and mathematical difficulties: An investigation of the role of basic numerical skills. - von Wirth, Elena; Kujath, Katharina; Ostrowski, Lea; Settegast, Ellen; Rosarius, Sarah; Döpfner, Manfred; Schwenk, Christin; Kuhn, Jörg-Tobias (Research in Developmental Disabilities, 2021)
Background: Attention-deficit/hyperactivity disorder (ADHD) and dyscalculia, also called mathematics disorder, frequently co-occur, yet the etiology of this comorbidity is poorly understood.Aims: This study investigated whether impairments in the understanding of numbers and magnitudes (basic numerical skills) are a unique risk factor for mathematical difficulties (MD) or a shared risk factor that could help to explain the association between ADHD and MD.Methods and Procedures: Basic numerical skills were assessed with eight subtests in children (age 6-10 years, N = 86) with clinically significant ADHD symptoms and/or MD and typically developing children (control group). This double dissociation design allowed to test for main and interaction effects of ADHD and MD using both classical and Bayesian analysis of variance (ANOVA).Outcomes and Results: Children with MD were impaired in transcoding, complex number and magnitude comparison, and arithmetic fact retrieval. They were not impaired in tasks assessing core markers of numeracy, which might be explained by the sample including children with mathematical difficulties instead of a diagnosed dyscalculia. ADHD was not associated with deficits in any of the tasks. The evidence for an additive combination of cognitive profiles was weak.Conclusions and Implications: Impairments in basic numerical skills are uniquely associated with MD and do not represent a shared risk factor for ADHD symptoms and MD.